A visual guide to Gospel events : fascinating insights into where they happened and why - Martin, James C.; Beck, John A., 1956-; Hansen, David G., 1938- (Grand Rapids, Mich. : Baker Books, 2014)
A visual guide to Gospel events, covering the life and ministry of Jesus, and including over three hundred full-color photographs and maps.
pt. 7. The arrest and trial of Jesus. Peter at the servant's seat ; Jesus prays in Gethsemane ; Peter cuts off the ear of the high priest's servant ; Peter's denial in the high priest's courtyard ; Judas throws money into the temple ; The purchase of the potter's field ; The problem with Pilate's quarters ; Pilate sends Jesus to Herod Antipas ; Pilate mocks the chief priests at the judge's seat ; Delayed verdict at the judge's seat -- pt. 8. The Crucifixion, Resurrection., and Ascension of Jesus. Crucified at Golgotha ; Crucified between two criminals ; Jesus dies on a cross ; Tearing the Temple curtain ; Joseph of Arimathea goes to Pilate ; Security at the tomb ; From Jerusalem to Emmaus and back ; Jesus meets the Apostles in the Galilee ; Jesus ascends from the Mount of Olives.
Includes bibliographical references (pages 195-199) and index.
Keywords: Jesus Christ -- Travel; Palestine -- Description and travel; Bible. -- Geography